THE INFLUENCE OF SOCIAL MEDIA MARKETING, BRAND IMAGE AND PRODUCT QUALITY PERCEPTION ON PURCHASING DECISIONS (Study on Consumers of Starbucks Coffee Shop Semarang) - Muhammad Ajib Syaifuddin; Ali Maskur (SEAN Institute, 2023)
A sample of 110 responfdents with purpose sempling techniques and methods in analyzing validity tests, reliability tests, t tests, determifnation coefficient (R2), F tedsts and multiple regression analysis with SPSS tool version 25 showked that Media Social marketing has a positiive and significant effect on the decision to purchase Starbucks product, Brand Image a positive and sigtnificant effect on the decisihon to purchase Starbucks product, and perception of product quality has positiive and significant effect on the decisinon to purchase product starbucks